Raynaud’s Phenomenon in A Patient with Scleroderma: A Case Report - Patricia Hutagalung; Kristo Alberto Nababan (Indonesian Journal of Global Health Research, 2025)
Systemic sclerosis, or scleroderma, is a chronic autoimmune disorder characterized by fibrosis of the skin and internal organs, vasculopathy, and immune dysregulation. Raynaud’s phenomenon (RP), marked by episodic vasospasm of the digital arteries in response to cold exposure or emotional stress, is often one of the earliest and most common sign of SSc. Early diagnosis plays a crucial role in preventing and managing complications of RP, such as digital ulcers and tissue damage due to chronic circulatory impairment, as well as in reducing long-term disability. This case report aims to highlight pedal ulcers as a complication of RP scleroderma and to emphasize the importance of early intervention in preventing progressive tissue damage. The data was conducted through a comprehensive approach including history assessment, physical examinations, electronic medical record reviews, laboratory diagnostics, and imaging studies to ensure accurate diagnosis and effective interventions. We report a 26-year-old woman who presented with a six-month history of progressive skin thickening and hardening involving almost all of her body. The patient also experienced finger stiffness, flexion contractures, and limited mouth opening. Dermatological examination revealed sclerotic skin with hypopigmented and hyperpigmented patches forming a "salt-and-pepper" appearance across various body areas, along with microstomia and a beaked nose. The Modified Rodnan Skin Score (mRSS) was 34. A diagnosis of systemic sclerosis was established based on the American College of Rheumatology in collaboration with the European League Against Rheumatism (ACR/EULAR) criteria. The patient was lost to follow-up after the initial visit and later returned with toe necrosis and ulceration over the ankle area. Treatment included systemic corticosteroids combined with methotrexate, along with counseling to avoid cold exposure and manage stress. Raynaud’s phenomenon should be recognized as a critical early sign of scleroderma. Comprehensive early evaluation, including autoantibody testing, is essential for timely diagnosis and the prevention of severe vascular complications.